2020
DOI: 10.1186/s12877-020-01743-0
|View full text |Cite
|
Sign up to set email alerts
|

Poor self-rated health predicts the incidence of functional disability in elderly community dwellers in Japan: a prospective cohort study

Abstract: Background Although previous large population studies showed elderly with poor self-rated health (SRH) to be at a high risk of functional disability in Western countries, there have been few studies in which the association between SRH and functional disability was investigated in Japanese community dwellers. The association between SRH and functional disability, defined as certification of the long-term care insurance (LTCI) system, in Japanese elderly community dwellers was examined in this study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies have strongly linked perceived health status with incident PFI in old age ( Gyasi and Phillips, 2018 , Yiengprugsawan et al, 2019 ). For example, Takahashi et al (2020) found in a prospective cohort study among older Japanese that poor self-rated health predicted increased functional disability. Using the WHO SAGE datasets, Tetteh et al (2019) observed 1.6 to 3.7-fold higher odds of functional difficulty in perceiving poor health in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have strongly linked perceived health status with incident PFI in old age ( Gyasi and Phillips, 2018 , Yiengprugsawan et al, 2019 ). For example, Takahashi et al (2020) found in a prospective cohort study among older Japanese that poor self-rated health predicted increased functional disability. Using the WHO SAGE datasets, Tetteh et al (2019) observed 1.6 to 3.7-fold higher odds of functional difficulty in perceiving poor health in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults with cancer not only suffer from cancer-generated health problems but also encounter other age-related medical conditions, which have been associated with increased FLs [ 58 ]. According to the findings of this study, previous research has reported that people with poor self-perceived health are at a high risk for FL in the non-cancer population [ 59 ]. Furthermore, it is believed that a worse self-perceived health is associated with inflammatory biomarkers, including C-reactive protein and cytokines, which may contribute to FL [ 60 ].…”
Section: Discussionmentioning
confidence: 51%
“…For health service research, the LTCI‐CNLs classification could be used for casemix adjustment; 18 for example, to examine the effectiveness of specific medical procedures, such as management of oral hygiene, on mortality among older patients. In previous outcome studies that focused on preventing long‐term care and used population‐based approaches, support level 1 or higher was considered to represent a disability, 20,21 and CN level 3 or higher was considered to show a loss of independence 22,23 . Our estimates showed gaps in WHODAS 2.0 and SARC‐F scores between CN level 1 and 2, and similarities in their scores between CN level 2 and 3 that might endorse CN level 2 or higher, which can be used to indicate a loss of independence in future outcome research among this population.…”
Section: Discussionmentioning
confidence: 83%